2019
DOI: 10.1021/acs.iecr.9b01137
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Synthesis of Ethyl Levulinate under Microwave and Nonmicrowave Heating Conditions

Abstract: The effects of microwave and nonmicrowave heating methods on the synthesis of ethyl levulinate (EL) from levulinic acid (LA) have been investigated in the present study. The levulinic acid esterification experiments were performed in the presence of silicotungstic acid catalyst and ethanol in a microwave and nonmicrowave instant heating reactor. An experimental fit of experimental data in a kinetic model suggested that LA esterification follows a pseudo-first-order reaction mechanism. Consequently, activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Herein, we describe the high activity of Pd‐HTs synthesized under continuous flow for selective aldehyde decarbonylation under microwave and conventional conditions, using low catalyst loadings and short reaction times, wherein activity and selectivity can be readily optimized. Microwave heating is advantageous in chemical synthesis and biomass processing owing to direct reactant heating as compared with slow conductive and convective heat transfer by conventional heating. This catalytic system does not require a promoter, soluble base, or the exclusion of air or water and provides a notable reduction in the precious metal loading and environmental impact compared with the state‐of‐the‐art catalysts (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we describe the high activity of Pd‐HTs synthesized under continuous flow for selective aldehyde decarbonylation under microwave and conventional conditions, using low catalyst loadings and short reaction times, wherein activity and selectivity can be readily optimized. Microwave heating is advantageous in chemical synthesis and biomass processing owing to direct reactant heating as compared with slow conductive and convective heat transfer by conventional heating. This catalytic system does not require a promoter, soluble base, or the exclusion of air or water and provides a notable reduction in the precious metal loading and environmental impact compared with the state‐of‐the‐art catalysts (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction rate ( r A ) for the proposed pseudohomogeneous reversible model is shown by eq , which is based on previous kinetics studies about microwave-assisted batch reactors. This expression attempts to describe both microwave and catalytic effects on the esterification route, which shows the dependence of r A with the molar concentrations of species ( C i ), the reaction time ( t ), the weight of catalyst ( W ), the reaction volume ( V ), the forward and reverse reaction constants ( k 1 and k 2 , respectively), and the reaction orders with respect to levulinic acid, n -butanol, n -butyl levulinate, and water (α, β, γ, and δ, respectively). d C A d t = r A = W V false( prefix− k 1 C A α C B β + k 2 C C γ C D δ false) The relationship between C i and the conversion of levulinic acid (X) is given by eq , where C i 0 is the initial molar concentration of species i and γ i is the stoichiometric coefficient of species i (positive for the products and negative for the reactants). C i = C A 0 true( C i 0 C A 0 + γ i X true) …”
Section: Methodsmentioning
confidence: 99%
“…However, very few studies have been reported using heterogeneous kinetic models , such as Langmuir–Hinshelwood–Hougen–Watson (LHHW) and Eley–Rideal (ER), which are commonly more suitable approaches for modeling the heterogeneous catalytic esterification of fatty acids than the pseudohomogeneous model, which simply assumes a power-law model that considers easy access of active sites by the reactants due to a complete swelling of catalyst and does not give a priority to the adsorption phenomenon . In addition, a pseudohomogeneous reversible model has been reported for studying the kinetics of the synthesis of levulinates assisted by microwaves, but to date, there have been no reports about kinetics studies with heterogeneous models for systems assisted with microwaves. Herein, this study aims to prepare a Preyssler-type heteropolyacid and evaluate it on the levulinic acid esterification for developing a suitable kinetic model, evaluating a pseudohomogeneous reversible model and heterogeneous kinetic models based on LHHW and ER mechanisms that can consider the microwaves and catalytic effects in the microwave-assisted batch reactor.…”
Section: Introductionmentioning
confidence: 99%
“…MW heating represents an important tool because it can reduce reaction time and energy consumption, thus improving the efficiency of the process [46,47]. In the specific case of LA esterification, remarkable thermal (kinetic) advantages of MW towards this reaction were already reported by Ahmad et al [48]. The choice of H 2 SO 4 as the acid catalyst was done taking into account its promising catalytic performances in the alcoholysis reaction to methyl and ethyl levulinates [49,50], while other acid catalysts, such as HCl or H 3 PO 4 , resulted less active, for example in the case of the one-pot reaction from cellulose to ethyl levulinate [49].…”
Section: Introductionmentioning
confidence: 98%